Canadian cinema since the 1980s : at the heart of the world - Pike, David L. (David Lawrence), 1963- (University of Toronto Press, 2012)
Making a significant advance in the study of the film industry of the period, Canadian Cinema since the 1980s is also an ideal text for students, researchers, and Canadian film enthusiasts.
Keywords: Motion pictures -- Canada -- History and criticism.; Motion picture producers and directors -- Canada.; Cinéma -- Canada -- Histoire et critique.; Producteurs et réalisateurs de cinéma -- Canada.; PERFORMING ARTS -- Film & Video -- History & Criticism.; PERFORMING ARTS -- Reference.; Motion picture producers and directors; Motion pictures; Canada; Electronic books.; Criticism, interpretation, etc.